Minimally invasive surgery of the head, neck, and cranial base (Lippincott Williams & Wilkins, 2005)
Medical College of Wisconsin, Milwaukee. Text, presented in atlas format, provides comprehensive coverage of optics, operative techniques, and complications. For subspecialists and general otolaryngologists. DNLM: Head--surgery.